Pengembangan Identitas Visual dan Strategi Branding Produk Gula Semut “Sekar Sari” sebagai Produk Unggulan Desa Pernasidi Menuju Pasar Premium - Miftahol Arifin; Nabila Noor Qisthani; Dian Novitasari; Aswan Munang (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The increasing demand for natural and healthy sweeteners has positioned coconut sugar as a high-value commodity, particularly within the premium market segment. However, coconut sugar producers in Pernasidi Village, Banyumas Regency, still face significant challenges in terms of branding and packaging design, limiting their access to modern markets. This community service program aims to develop the visual identity and branding strategy of the “Sekar Sari” coconut sugar product as a leading village product ready to compete in premium markets. The method employed is a participatory co-design approach, involving field observations, exploration of local brand values, interviews with stakeholders, and collaborative design workshops with local producers. The program has resulted in a professional logo, an authentic brand narrative, and eco-friendly packaging design, all of which have been directly implemented in product production and promotion activities. Initial outcomes show an improvement in market perception of the product’s image, increased partner satisfaction with the new presentation, and the producers’ readiness to enter retail and digital sales channels. Beyond its visual impact, this branding process has also fostered a sense of ownership and pride among community members toward their local product. It is concluded that strategic branding, developed through inclusive and contextual methods, can serve as a key driver for economic transformation in rural areas through local product empowerment